PENGARUH STRUKTUR MODAL DAN NPL PADA PERTUMBUHAN ASET SERTA IMPLIKASINYA TERHADAP ROA PADA LPD KABUPATEN TABANAN - Prasetya P, Gd Agus Yudha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
Return On Assets (ROA) is an important ratio that can be used to measure the ability of a company with investments that have been invested (assets it has) to make a profit. This study aims to determine the effect of capital structure and Non-Performing Loans on Return On Assets (ROA) of companies through asset growth. The population of this study were LPDs recorded in the LPLPD of the Tabanan Regency for the period 2013 - 2014 totaling 307 LPDs. In the selection of samples carried out by purposive sampling method with the criteria of healthy LPD recorded in the LPLPD of Tabanan Regency for the period 2013-2014 and compiling annual financial reports in a row in 2013 - 2014 to obtain as many as 40 healthy LPDs. The results of the analysis show that the capital structure and Non Performing Loans can have a direct effect on asset growth and Return On Assets (ROA), as well as the capital structure and Non Performing Loans can have an indirect effect on Return On Assets (ROA) through asset growth.